Inhibition of matrix metalloproteins 9 attenuated Candida albicans induced inflammation in mouse cornea - Dong, C.; Yang, M. G. (Cellular and Molecular Biology, 2016)
Since the severe corneal ulceration of mouse cornea is known to occur with inflammation. As one of imperative matrix metalloproteinase, the potential roles of matrix metalloproteins 9 (MMP9) in corneal ulceration and keratitis are still unveiled caused by fungal invasion. In this study, Candida albicans (CA) inoculated wild-type KM mice cornea was used as a model pathogen in corneal inflammation.  CA invasion significantly stimulated the expression of collagen IV and MMP9 detected by RT-PCR, Real-time PCR and Immunofluorescent staining in mouse cornea as soon as 6 hours post infection, and relatively decreased at 1 day post infection. For examining the role of MMP9 in fungal keratitis, the mice corneas were subconjunctivally injected MMP9 antibody or recombinant MMP9 protein 6 hours prior to CA inoculation, using rabbit IgG as control. Subconjunctival injection of recombinant MMP9 protein prior to CA inoculation enhanced, whereas MMP9 antibody attenuated corneal ulceration and inflammation, examining basement membrane, fungal load, myeloperoxidase (MPO) and proinflammatory cytokines including Macrophage inflammatory protein 2 (MIP2), Interleukin-1Î² (IL-1Î²) and Tumor necrosis factor-Î± (TNF-Î±). Inhibition of MMP9 could potentially attenuate Candida albicans induced inflammation in mouse cornea.